Composite current collector and application thereof
By introducing a shrinkable thermally sensitive conductive structure into the current collector of the lithium-ion battery, the problem that the current collector is prone to internal short circuit under stress is solved, and the effect of improving the conductive performance while ensuring safety performance is achieved.
Patent Information
- Application Number
- CN202411353708.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-12
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing lithium-ion battery current collectors are prone to internal short circuits when subjected to mechanical, thermal or electrical stress, resulting in thermal runaway and safety accidents, and the introduction of flame retardants will reduce the conductivity.
A composite liquid collector is adopted, and its structure includes a functional layer on both sides of the current collector base layer and a shrinkable thermally conductive structure that penetrates the functional layer and the current collector base layer. When the temperature rises, the conductive structure shrinks, breaking the electrical connection of the metal layer and releasing flame retardant, thereby preventing heat from getting out of control.
Effectively prevent lithium-ion batteries from getting out of control in abnormal situations, improve safety performance, while maintaining good conductivity and reducing battery internal resistance.
Smart Images

Figure CN119419280A_ABST
Abstract
Description
[0001] This application claims the priority of the Chinese patent application filed with the China Patent Office on August 12, 2024, with application number 202411099248.8 and application name “A composite current collector and its application”, all contents of which are incorporated by reference into this application. Technical Field
[0002] The invention relates to a composite current collector and application thereof, belonging to the field of electrochemistry. Background Art
[0003] Secondary batteries, represented by lithium-ion secondary batteries, are widely used in electric vehicles and consumer electronics due to their advantages of high energy density, high output power, long cycle life and low environmental pollution. With the continuous development and large-scale application of the battery industry, people have higher and higher requirements for the quality density and safety of batteries.
[0004] As one of the core components of the battery, the performance of the current collector directly affects the mass density and safety of the battery. Among them, the current collectors used in traditional batteries are mostly metal current collectors. However, when metal current collector batteries are damaged by mechanical stress (especially extrusion, puncture, impact), thermal stress or electrical stress, internal short circuits are prone to occur, causing thermal runaway of the battery and leading to safety accidents. Therefore, giving the battery current collector flame retardant properties is one of the effective means to reduce the problem of internal short circuits in the current collector, prevent thermal runaway, and improve safety.
[0005] At present, safety performance is usually achieved by introducing flame retardants into the current collector. However, the introduction of flame retardants will reduce the conductivity of the current collector, which seriously limits the development of batteries. How to improve the conductivity of the current collector while ensuring the safety performance of the battery has become an urgent problem to be solved in this field. Summary of the invention
[0006] In view of the problems of the above-mentioned prior art, the present invention provides a composite current collector. By improving the structure and composition of the composite current collector, after the current collector is used in a lithium-ion battery, when the lithium-ion battery has abnormal conditions such as puncture, extrusion, collision, etc., resulting in an internal short circuit, the lithium-ion battery can be prevented from thermal runaway, thereby improving the safety performance of the lithium-ion battery. At the same time, the current collector also has good conductive properties, which can reduce the internal resistance of the lithium-ion battery.
[0007] The present invention also provides a pole piece, comprising the above-mentioned current collector.
[0008] In one aspect, the present invention provides a composite current collector, comprising a current collector substrate, a first functional layer and a second functional layer respectively located on both sides of the current collector substrate, and N shrinkable thermosensitive conductive structures, N≥1;
[0009] Wherein, in a direction gradually away from the current collector substrate, the first functional layer at least includes a gel layer and a metal layer stacked, and the second functional layer at least includes a gel layer and a metal layer stacked;
[0010] The gel layer includes a polymer matrix and a flame retardant;
[0011] When the application temperature is lower than the shrinkage temperature of the shrinkable thermosensitive conductive structure, the shrinkable thermosensitive conductive structure penetrates the first functional layer, the second functional layer, and the current collector base layer, and electrically connects the metal layer of the first functional layer and the metal layer of the second functional layer;
[0012] When the application temperature is greater than the shrinking temperature, the shrinkable thermosensitive conductive structure shrinks, the metal layer of the first functional layer and the metal layer of the second functional layer are electrically disconnected, and the flame retardant is released.
[0013] The composite current collector as described above, wherein the shrinkage temperature of the shrinkable thermosensitive conductive structure is 90-150°C.
[0014] In the composite current collector as described above, the shrinkable thermosensitive conductive structure accounts for 20%-60% of the surface area of the composite current collector.
[0015] In the composite current collector as described above, the mass ratio of the polymer matrix to the flame retardant is 1:(0.1%-5%).
[0016] The composite current collector as described above, wherein the first functional layer and the second functional layer further independently include a bonding layer, and the bonding layer is located between the gel layer and the metal layer;
[0017] And / or, the bonding layer comprises at least one of aramid, polyethylene, hydroxyl-modified silicon oxide particles, and a mixture of silicon oxide and polyacrylic acid resin;
[0018] And / or, the bonding layer has a thickness of 0.01-1 μm.
[0019] The composite current collector as described above, wherein the shrinkable thermosensitive conductive structure penetrates the current collector substrate and protrudes from the surface of the first functional layer;
[0020] And / or, the shrinkable thermosensitive conductive structure penetrates the current collector substrate and protrudes from the surface of the second functional layer.
[0021] As for the composite current collector as described above, the length of the shrinkable thermosensitive conductive structure protruding from the surface of the first functional layer is L1, and the thickness of the composite current collector is L, which satisfies: L1 / L=1% to 10%;
[0022] And / or, the length of the shrinkable thermosensitive conductive structure protruding from the surface of the second functional layer is L2, and the thickness of the composite current collector is L, which satisfies: L2 / L=1% to 10%.
[0023] The composite current collector as described above, wherein the material of the shrinkable thermosensitive conductive structure is selected from bismuth-tin alloy or tin-indium alloy; and / or, the polymer matrix comprises a cross-linked polymer containing an EO main chain and an amide group block;
[0024] And / or, the flame retardant is a phosphorus-based flame retardant;
[0025] And / or, the current collector substrate is selected from a PET layer or a PVDF layer;
[0026] And / or, the metal layer is selected from copper or aluminum.
[0027] The composite current collector as described above, wherein the current collector substrate has a thickness of 1-10 μm;
[0028] And / or, the gel layer has a thickness of 1-5 μm;
[0029] And / or, the thickness of the metal layer is 0.01-1 μm;
[0030] And / or, the shrinkable thermosensitive conductive structure has a length of 2.5-17 μm.
[0031] Another aspect of the present invention provides a pole piece, comprising the composite current collector as described above.
[0032] The composite current collector provided by the present invention, by arranging functional layers on both sides of the current collector base layer and a shrinkable thermosensitive conductive structure penetrating the functional layers and the current collector base layer, enables a lithium ion battery including the composite current collector to effectively avoid thermal runaway in abnormal situations and improve the lithium ion safety performance; at the same time, the composite current collector with the shrinkable thermosensitive conductive structure also has good conductivity and can reduce the resistance of the lithium ion battery.
[0033] The pole piece provided by the present invention comprises the composite current collector, so the pole piece has good safety performance and conductive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A structural diagram of a composite current collector provided in one specific embodiment of the present invention;
[0035] Figure 2 A structural diagram of a composite current collector provided in Example 6 of the present invention;
[0036] Figure 3 A structural diagram of the composite current collector provided in Examples 3, 4, and 5 of the present invention;
[0037] Figure 4 A structural diagram of the composite current collector provided in Examples 1 and 2 of the present invention;
[0038] Figure 5 This is a structural diagram of the composite current collector provided in Comparative Example 4 of the present invention.
[0039] Figure numerals: 1 - current collector substrate; 21 - first functional layer, 22 - second functional layer; 201 - gel layer; 202 - metal layer; 203 - adhesive layer; 3 - shrinkable thermosensitive conductive structure. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In one aspect, the present invention provides a composite current collector, such as Figure 1 As shown, it includes a current collector substrate 1, a first functional layer 21 and a second functional layer 22 respectively located on both sides of the current collector substrate, and N shrinkable thermosensitive conductive structures 3, N ≥ 1; wherein, in the direction gradually away from the current collector substrate 1, the first functional layer 21 at least includes a gel layer 201 and a metal layer 202 arranged in a stacked manner, and the second functional layer 22 at least includes a gel layer 201 and a metal layer 202 arranged in a stacked manner; the gel layer 201 includes a polymer matrix and a flame retardant; when the application temperature is lower than the shrinkage temperature of the shrinkable thermosensitive conductive structure 3, the shrinkable thermosensitive conductive structure 3 penetrates the first functional layer 21, the second functional layer 22, and the current collector substrate 1, and electrically connects the metal layer 202 of the first functional layer 21 and the metal layer 202 of the second functional layer 22; when the application temperature is higher than the shrinkage temperature, the shrinkable thermosensitive conductive structure 3 shrinks, the metal layer 201 of the first functional layer 21 and the metal layer 202 of the second functional layer 22 are electrically disconnected, and the flame retardant is released.
[0042] The application temperature in the present invention refers to the ambient temperature of the composite current collector.
[0043] Among them, the shrinkable thermosensitive conductive structure 3 in the present invention includes a shrinkable thermosensitive conductive material, and the shrinkable thermosensitive conductive material has the characteristic of shrinking in volume after the application temperature is higher than the shrinkage temperature. Therefore, when the application temperature of the shrinkable thermosensitive conductive structure 3 including the shrinkable thermosensitive conductive material is lower than the shrinkage temperature of the shrinkable thermosensitive conductive structure 3, the shrinkable thermosensitive conductive structure 3 penetrates the current collector base layer 1, the first functional layer 21 and the second functional layer 22, and electrically connects the metal layer of the first functional layer 21 with the metal layer of the second functional layer 22; when the application temperature is higher than the shrinkage temperature, the shrinkable thermosensitive conductive structure 3 shrinks, and the metal layer of the first functional layer 21 and the metal layer of the second functional layer 22 are electrically disconnected. When the metal layer of the first functional layer 21 and the metal layer of the second functional layer 22 are electrically disconnected, the current collector is electrically disconnected, the impedance of the battery is increased, the thermal runaway of the battery is prevented from spreading, and the safety of the battery is improved.
[0044] The shrinkable thermosensitive conductive structure 3 may be in the shape of a rod, a sphere, a mesh, a truncated cone, or the like.
[0045] The present invention does not limit the specific preparation process of the composite current collector, and a common preparation process in the art can be selected according to actual conditions.
[0046] In a specific embodiment, the gel layer 201 and the current collector substrate 1 can be bonded together by hot melt bonding or chemical bonding.
[0047] When a short circuit or a partial short circuit occurs in the battery, causing the temperature inside the battery cell to rise, and the application temperature is greater than the shrinking temperature, the shrinkable thermosensitive conductive structure 3 shrinks, exposing the gel layer 201, and then the flame retardant in the gel layer is released, increasing the flame retardancy of the composite current collector, increasing the thermal failure temperature of the electrode, and capturing hydrogen free radicals and hydroxyl free radicals when sparks appear at the electrode, while releasing inert gas to achieve a flame retardant effect and further improve the safety of the battery. At the same time, this setting can effectively prevent the contact between the flame retardant and the electrolyte when the battery does not suffer from thermal failure, and does not affect the electrochemical performance of the battery.
[0048] According to the technical solution provided by the present invention, after the composite current collector is applied to a lithium-ion battery, the conductivity of the composite current collector can be improved and the internal resistance of the current collector can be reduced when in use. When a short circuit inside the battery causes thermal runaway, the safety of the battery can be improved by electrically disconnecting the circuit. Based on this phenomenon, the inventor analyzed and believed that it may be that: in use, the shrinkable thermosensitive conductive structure 3 connects the metal layer 202 and the current collector matrix 1, thereby improving the conductivity. In the thermal runaway state, the shrinkable thermosensitive conductive structure 3 shrinks in volume, causing an electrical disconnection between the metal layer and the current collector matrix, causing the current collector to lose electrical connection, increasing the impedance of the battery, preventing the thermal runaway of the battery from spreading, and improving the safety of the battery.
[0049] Furthermore, in a specific embodiment of the present invention, the shrinkage temperature of the shrinkable thermosensitive conductive structure is 90-150°C.
[0050] In detail, the shrinkage temperature of the shrinkable thermosensitive conductive structure includes but is not limited to 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C. or a range between any two thereof.
[0051] It can be understood that the type of shrinkable thermosensitive conductive structure can be selected from a material type that meets the above shrinking temperature. In a specific embodiment, the type of shrinkable thermosensitive conductive structure is selected from a bismuth-tin alloy or a tin-indium alloy.
[0052] When the shrinkage temperature of the shrinkable thermosensitive conductive structure is greater than or equal to 90°C, the shrinkable thermosensitive conductive structure has more excellent temperature responsiveness, can more accurately control the electrical connection at different application temperatures, and improve the safety and conductivity of the battery.
[0053] It is understandable that a suitable number of shrinkable thermosensitive conductive structures 3 can be provided according to the surface area of the composite current collector. Further, in a specific embodiment of the present invention, the shrinkable thermosensitive conductive structure 3 occupies 20%-60% of the surface area of the composite current collector.
[0054] The area ratio of the shrinkable thermosensitive conductive structure 3 on the surface of the composite current collector refers to the ratio of the cross-sectional area of the shrinkable thermosensitive conductive structure 3 on the surface of the composite current collector to the surface area of the entire composite current collector.
[0055] In detail, the area ratio of the shrinkable thermosensitive conductive structure on the surface of the composite current collector includes but is not limited to 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range between any two of them.
[0056] When the area ratio of the shrinkable thermosensitive conductive structure 3 on the surface of the composite current collector is within the above range, the electrical connection function of the shrinkable thermosensitive conductive structure can be fully exerted to improve the conductivity, while the mechanical properties of the composite current collector can be guaranteed.
[0057] The flame retardant in the present invention can be a flame retardant with high temperature volatility, such as a phosphorus-based flame retardant, and the polymer matrix can be a cross-linked polymer containing an EO main chain and an amide group block. Further, in a specific embodiment of the present invention, the mass ratio of the polymer matrix to the flame retardant is 1: (0.1%-5%).
[0058] In detail, the mass ratio of the polymer matrix to the flame retardant includes but is not limited to 1:0.1%, 1:0.5%, 1:1%, 1:2%, 1:3%, 1:4%, 1:5% or a range composed of any two thereof.
[0059] When the mass ratio of the polymer matrix to the flame retardant is within the above range, not only can the flame retardant effect of the flame retardant be fully exerted, but also the role of the polymer matrix can be exerted to improve the mechanical properties of the gel layer.
[0060] Further, in a specific embodiment of the present invention, the structure of the composite current collector is as shown in Figure 2 As shown, the first functional layer 21 and the second functional layer 22 further independently include an adhesive layer 203 , and the adhesive layer 203 is located between the gel layer 201 and the metal layer 202 .
[0061] The bonding layer 203 may be selected from inorganic or organic substances containing polar groups. The inorganic substances containing polar groups include but are not limited to any one or more of silicon oxide, zinc oxide, copper oxide, graphite, graphene, graphene oxide and carbon nanotubes grafted with hydroxyl or carboxyl groups, and the organic substances include but are not limited to any one or more of aramid, polyacrylic resin, epoxy resin and cyanoacrylate.
[0062] The present invention does not limit the specific process for connecting the adhesive layer 203 with the gel layer 201 and the metal layer 202 , and a common process in the art, such as coating, etc., may be selected.
[0063] In the present invention, the bonding layer 203 can enhance the bonding force between the gel layer 201 and the metal layer 202, prevent the metal layer 202 from falling off, and further improve the mechanical strength of the composite current collector.
[0064] Further, in a specific embodiment of the present invention, the bonding layer 203 includes at least one of aramid, polyethylene, hydroxyl-modified silica particles, and a mixture of silica and polyacrylic acid resin; and / or the bonding layer 203 has a thickness of 0.01-1 μm.
[0065] The present invention does not limit the specific particle size of the hydroxyl-modified silicon oxide particles in the bonding layer 203 , and a suitable particle size, such as 50-1000 nm, can be selected according to actual conditions.
[0066] When the material of the bonding layer 203 is within the above range, it has a more excellent bonding effect and can further improve the mechanical properties of the composite current collector.
[0067] Further, in a specific embodiment of the present invention, Figure 3As shown, the shrinkable thermosensitive conductive structure 3 penetrates the current collector substrate 1 and protrudes from the surface of the first functional layer 21 ; and / or, the shrinkable thermosensitive conductive structure 3 penetrates the current collector substrate 1 and protrudes from the surface of the second functional layer 22 .
[0068] When the shrinkable thermosensitive conductive structure 3 penetrates the current collector substrate 1 and protrudes from the surface of the first functional layer 21 , the projected length of the shrinkable thermosensitive conductive structure along the thickness direction of the composite current collector is greater than the thickness of the composite current collector.
[0069] Similarly, when the shrinkable thermosensitive conductive structure 3 penetrates the current collector substrate 1 and protrudes from the surface of the first functional layer 21, the projected length of the shrinkable thermosensitive conductive structure along the thickness direction of the composite current collector is higher than the thickness of the composite current collector.
[0070] It is understandable that, in order to facilitate subsequent processes, the size of the protruding portion needs to be controlled according to actual conditions.
[0071] Further, in one embodiment of the present invention, the structure of the composite current collector is as follows: Figure 3 As shown, the length of the shrinkable thermosensitive conductive structure protruding from the surface of the first functional layer is L1, and the thickness of the composite current collector is L, which satisfies: L1 / L=1%~10%; and / or, the length of the shrinkable thermosensitive conductive structure protruding from the surface of the second functional layer is L2, and the thickness of the composite current collector is L, which satisfies: L2 / L=1%~10%.
[0072] In detail, L1 / L includes but is not limited to 1%, 2%, 4%, 6%, 8%, 10% or any range between them; L2 / L includes but is not limited to 1%, 2%, 4%, 6%, 8%, 10% or any range between them. When the relationship between the length of the protruding portion and the thickness of the current collector meets the above range, it can not only improve the bonding stability of the composite current collector, ensure the mechanical strength of the composite current collector, but also meet the process requirements.
[0073] Further, in a specific embodiment of the present invention, the material of the shrinkable thermosensitive conductive structure 3 is selected from bismuth-tin alloy or tin-indium alloy; and / or, the polymer matrix includes a cross-linked polymer containing an EO main chain and an amide group block;
[0074] and / or, the flame retardant is a phosphorus-based flame retardant;
[0075] and / or, the current collector substrate 1 is selected from a PET layer or a PVDF layer;
[0076] And / or, the metal layer 202 is selected from copper or aluminum.
[0077] In detail, bismuth-tin alloy and tin-indium alloy have good electrical conductivity and excellent thermal sensitivity. When thermal runaway occurs in the battery, they can respond immediately and improve the safety of the battery.
[0078] The polymer matrix of the present invention comprises a cross-linked polymer containing an EO main chain and an amide group block, wherein the EO main chain is derived from diglycidyl ether, cyclic lactone, and ethylene glycol dimethacrylate; and the amide group is derived from cyclic lactam and unsaturated hydrocarbon amide.
[0079] The polymer matrix in the present invention can not only improve the mechanical strength of the gel layer 201, but also has good chemical compatibility with the flame retardant, the current collector base layer 1 and the adhesive layer 203, thereby preventing the composite current collector from slipping and falling off during application.
[0080] The phosphorus-based flame retardant in the present invention refers to a phosphate flame retardant, such as triethyl phosphate, dimethyl phosphate, and the like.
[0081] Phosphorus-based flame retardants can not only effectively reduce the combustion performance of materials, release phosphate compounds at high temperatures to form a protective layer, but also have good compatibility and can fully play their role in composite current collectors.
[0082] Further, in a specific embodiment of the present invention, the thickness of the current collector substrate 1 is 1-10 μm; and / or the thickness of the gel layer 201 is 1-5 μm; and / or the thickness of the metal layer 202 is 0.01-1 μm; and / or the length of the shrinkable thermosensitive conductive structure 3 in the extension direction is 2.5-17 μm.
[0083] When the thickness or length of each structure of the composite current collector is within the above range, the battery including the composite current collector has more excellent conductivity and flame retardant properties, and also has higher mechanical properties, because: the shrinkable thermosensitive conductive structure connects the conductive layers on both sides of the polymer base layer to form an electron path, which greatly reduces the resistance of the composite current collector; the flame retardant is encapsulated in the gel layer, isolating it from the contact with the electrolyte without affecting the electrochemical properties of the battery, and when the battery has thermal runaway or short circuit and causes the electrode to be heated, the shrinkable thermosensitive conductive structure shrinks in volume to form a flame retardant release channel, and the flame retardant is released in the electrode to improve the flame retardant performance of the battery; the adhesion between the current collector base layer and the metal layer is improved by setting the gel layer, and at the same time, a polymer base layer is set inside the gel layer, which contains a cross-linked polymer, which greatly improves the mechanical strength of the first functional layer and the second functional layer, and gives high adhesion performance while enhancing the mechanical strength of the composite current collector.
[0084] The present invention also provides a pole piece, comprising the composite current collector as described above.
[0085] The electrode sheet provided by the present invention includes any one of a positive electrode sheet and a negative electrode sheet. It can be understood that the electrode sheet also includes an active layer formed by an active material.
[0086] The present invention does not limit the specific preparation method of the electrode sheet. Taking the composite current collector for the positive electrode sheet as an example, when preparing the positive electrode sheet, for example, the positive electrode active material, the conductive agent and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the composite current collector, and the positive electrode sheet is obtained after drying, rolling and slitting.
[0087] In a specific embodiment, the positive electrode active layer includes 70-99 wt % of positive electrode active material, 0.5-15 wt % of conductive agent, and 0.5-15 wt % of binder in terms of mass percentage.
[0088] Among them, the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polymers containing ethylene oxide, polyvinyl pyrrolidone, and polyurethane.
[0089] It can be understood that a battery including the composite current collector as described above or the electrode sheet as described above can be developed.
[0090] It is conceivable that the battery of the present invention includes, in addition to the above-mentioned pole pieces, an electrolyte and a separator.
[0091] The present invention does not strictly limit the selection of the electrolyte, and can include one or more of the solvents commonly used in the current battery electrolyte, and the electrolyte lithium salts commonly used in the current lithium ion electrolyte, for example: the solvent can be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, cyclopentane, γ-butyrolactone, etc.; the lithium salt can be, for example, lithium hexafluorophosphate (LiPF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0092] The present invention does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in current batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.
[0093] The battery of the present invention can be manufactured by conventional methods known to those skilled in the art.
[0094] In a specific embodiment, when preparing a battery, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery, and the battery is placed, formed and sealed for the second time to complete the preparation of the battery.
[0095] Hereinafter, the composite current collector provided by the present invention will be described in detail through specific embodiments.
[0096] Example 1
[0097] The structure of the composite current collector provided in this embodiment is shown in FIG. Figure 4 As shown, the preparation method of the composite current collector comprises the following steps:
[0098] 1. PET and heat-shrinkable thermosensitive conductive agent indium tin alloy are compounded by mechanical rolling to obtain a composite layer in which the shrinkable thermosensitive conductive structure 3 penetrates the current collector base layer 1. The thickness of the PET layer as the current collector base layer 1 is 1 μm, and the indium tin alloy is spherical with a diameter of 17 μm.
[0099] 2. A gel precursor is coated on both sides of the composite layer, comprising a polymer matrix (ether monomer polyethylene glycol ethyl methacrylate, amide monomer hydroxyethyl acrylamide), an initiator AIBN and a flame retardant triethyl phosphate, wherein the mass ratio of the polymer matrix to the flame retardant is 1:3%, and a gel layer 201 is obtained by light / heat curing, and the thickness of the gel layer 201 is 1 μm.
[0100] 3. The aramid film is pressed onto the surface of the gel layer 201 away from the current collector substrate 1 by mechanical rolling to modify the adhesive layer 203 of hydroxyl-modified silicon oxide, and the thickness of the adhesive layer 203 is 0.05 μm.
[0101] 4. The copper metal layer 202 is modified on the surface of the hydroxyl-modified silicon oxide of the bonding layer 203 by chemical vapor deposition. The thickness of the copper metal layer 202 is 0.05 μm, and finally a composite current collector is obtained. The shrinkable thermosensitive conductive structure 3 accounts for 45% of the surface area of the composite current collector.
[0102] Example 2
[0103] The structure of the composite current collector provided in this embodiment is shown in FIG. Figure 4 As shown, the preparation method of the composite current collector comprises the following steps:
[0104] 1. PVDF is dissolved in NMP and mixed with a heat-shrinkable thermosensitive conductive agent bismuth-tin alloy to form a suspension. The shrinkable thermosensitive conductive structure 3 is made into a composite layer penetrating the current collector substrate 1 by a solution casting method. The thickness of the PVDF layer as the current collector substrate 1 is 2 μm, and the shrinkable thermosensitive conductive structure 3 is spherical with a diameter of 15 μm.
[0105] 2. Coat the two sides of the composite layer with a gel precursor, including a polymer matrix (polyether polymer matrix ethylene glycol ethyl methacrylate) and a flame retardant dimethyl phosphate, wherein the mass ratio of the polymer matrix to the flame retardant is 1:5%. After standing for 30 minutes, a gel layer 201 is obtained, and the thickness of the gel layer 201 is 1.5 μm.
[0106] 3. The aramid film is pressed onto the surface of the gel layer 201 by mechanical roller to modify the bonding layer 203 of hydroxyl-modified silicon oxide, and the thickness of the bonding layer 203 is 0.08 μm.
[0107] 4. The aluminum metal layer 202 is modified on the surface of the bonding layer 203 by physical vapor deposition. The thickness of the aluminum metal layer 202 is 0.07 μm. Finally, a composite current collector is obtained. The shrinkable thermosensitive conductive structure 3 accounts for 20% of the surface area of the composite current collector.
[0108] Example 3
[0109] The structure of the composite current collector provided in this embodiment is shown in FIG. Figure 3 As shown, the preparation method of the composite current collector comprises the following steps:
[0110] 1. PVDF is dissolved in NMP and mixed with a heat-shrinkable thermosensitive conductive agent bismuth-tin alloy to form a suspension. The shrinkable thermosensitive conductive structure 3 is made into a composite layer that penetrates the current collector substrate 1 by a solution casting method. The thickness of the PVDF layer as the current collector substrate 1 is 2 μm. The shrinkable thermosensitive conductive structure 3 is rod-shaped with a side length of 100 nm and a length of 5 μm.
[0111] 2. Coat the two sides of the composite layer with a gel precursor, including a polymer matrix (polyether polymer matrix ethylene glycol ethyl methacrylate) and a flame retardant dimethyl phosphate, wherein the mass ratio of the polymer matrix to the flame retardant is 1:0.1%. After standing for 30 minutes, a gel layer 201 is obtained, and the thickness of the gel layer 201 is 1 μm.
[0112] 3. The aramid film is pressed onto the surface of the gel layer 201 by a mechanical roller to modify the adhesive layer 203, and the thickness of the adhesive layer 203 is 0.02 μm.
[0113] 4. The aluminum metal layer 202 is modified on the surface of the bonding layer 203 by physical vapor deposition. The thickness of the aluminum metal layer 202 is 0.02 μm. Finally, a composite current collector is obtained. The shrinkable thermosensitive conductive structure 3 accounts for 60% of the surface area of the composite current collector.
[0114] Example 4
[0115] The structure of the composite current collector provided in this embodiment is shown in FIG. Figure 3 As shown, the preparation method of the composite current collector comprises the following steps:
[0116] 1. PVDF was dissolved in NMP and mixed with a heat-shrinkable thermosensitive conductive agent, bismuth-tin alloy, to form a suspension. The shrinkable thermosensitive conductive structure 3 was made into a composite layer penetrating the current collector substrate 1 by a solution casting method. The thickness of the PVDF layer as the current collector substrate 1 was 0.5 μm. The shrinkable thermosensitive conductive structure 3 was rod-shaped with a side length of 100 nm and a length of 5 μm.
[0117] 2. Coat the two sides of the composite layer with a gel precursor, including a polymer matrix (polyether polymer matrix ethylene glycol ethyl methacrylate) and a flame retardant dimethyl phosphate, wherein the mass ratio of the polymer matrix to the flame retardant is 1:3%. After standing for 30 minutes, a gel layer 201 is obtained, and the thickness of the gel layer 201 is 0.5 μm.
[0118] 3. The aramid film is pressed onto the surface of the gel layer 201 by a mechanical roller to modify the adhesive layer 203, and the thickness of the adhesive layer 203 is 0.01 μm.
[0119] 4. The aluminum metal layer 202 is modified on the surface of the bonding layer 203 by physical vapor deposition. The thickness of the aluminum metal layer 202 is 0.05 μm. Finally, a composite current collector is obtained. The shrinkable thermosensitive conductive structure 3 accounts for 45% of the surface area of the composite current collector.
[0120] Example 5
[0121] The structure of the composite current collector provided in this embodiment is shown in FIG. Figure 3 As shown, the preparation method of the composite current collector comprises the following steps:
[0122] 1. PVDF is dissolved in NMP and mixed with a heat-shrinkable thermosensitive conductive agent bismuth-tin alloy to form a suspension. The shrinkable thermosensitive conductive structure 3 is made into a composite layer that penetrates the current collector substrate 1 by a solution casting method. The thickness of the PVDF layer as the current collector substrate 1 is 2 μm. The shrinkable thermosensitive conductive structure 3 is rod-shaped with a side length of 100 nm and a length of 5 μm.
[0123] 2. A gel precursor is coated on both sides of the composite layer, comprising a polymer matrix (polyether polymer matrix ethylene glycol ethyl methacrylate) and a flame retardant magnesium hydroxide, wherein the mass ratio between the polymer matrix and the flame retardant is 1:3.5%. After standing for 30 minutes, a gel layer 201 is obtained, and the thickness of the gel layer 201 is 1 μm.
[0124] 3. The aramid film is pressed onto the surface of the gel layer 201 by a mechanical roller to modify the adhesive layer 203 PVDF, and the thickness of the adhesive layer 203 is 0.02 μm.
[0125] 4. The aluminum metal layer 202 is modified on the surface of the bonding layer 203 by physical vapor deposition. The thickness of the aluminum metal layer 202 is 0.02 μm. Finally, a composite current collector is obtained. The shrinkable thermosensitive conductive structure 3 accounts for 30% of the surface area of the composite current collector.
[0126] Example 6
[0127] The structure of the composite current collector provided in this embodiment is shown in FIG. Figure 2 As shown, the preparation method of the composite current collector comprises the following steps:
[0128] 1. PVDF is dissolved in NMP and mixed with a heat-shrinkable thermosensitive conductive agent bismuth-tin alloy to form a suspension. The shrinkable thermosensitive conductive structure 3 is made into a composite layer that penetrates the current collector substrate 1 by a solution casting method. The thickness of the PVDF layer as the current collector substrate 1 is 2 μm. The shrinkable thermosensitive conductive structure 3 is rod-shaped with a side length of 100 nm and a length of 5 μm.
[0129] 2. Coat the two sides of the composite layer with a gel precursor, including a polymer matrix (polyether polymer matrix ethylene glycol ethyl methacrylate) and a flame retardant dimethyl phosphate, wherein the mass ratio of the polymer matrix to the flame retardant is 1:3%. After standing for 30 minutes, a gel layer 201 is obtained, and the thickness of the gel layer 201 is 1 μm.
[0130] 3. The aramid film is pressed onto the surface of the gel layer 201 by a mechanical roller to modify the adhesive layer 203, and the thickness of the adhesive layer 203 is 0.02 μm.
[0131] 4. The aluminum metal layer 202 is modified on the surface of the bonding layer 203 by physical vapor deposition, so that the metal layer 202 just covers the protruding points of the shrinkable thermosensitive conductive structure. The thickness of the aluminum metal layer 202 is 0.98 μm, and finally a composite current collector is obtained. The shrinkable thermosensitive conductive structure 3 accounts for 60% of the area on the surface of the composite current collector.
[0132] Comparative Example 1
[0133] The preparation method of the current collector provided in this comparative example comprises the following steps:
[0134] 1. Prepare a through-hole PET film by laser punching a 2 μm PET film.
[0135] 2. A copper metal layer 202 is formed on both sides of the PET film by physical vapor deposition, thereby obtaining a composite current collector with PET as the base layer and copper metal layers 202 on both sides.
[0136] Comparative Example 2
[0137] The preparation method of the current collector provided in this comparative example comprises the following steps:
[0138] 1. Preparation of base film: PET (polyethylene terephthalate) and PI (polyimide) emulsion were mixed in a mass ratio of 80:20 to prepare a slurry; the slurry was subjected to electrostatic spinning (voltage of 4.0 KV, melt viscosity of 1000 pcs, nozzle diameter of 0.1 μm) to prepare a base film (through-hole diameter of 0.2 μm, porosity of 50%, thickness of 5 μm);
[0139] 2. Preparation of high molecular polymer film: The phosphorus-based flame retardant triethyl phosphate is coated on the base film by a spray coating process (coating temperature is 80°C, coating unwinding tension is 10N, winding tension is 10N, stretching speed is 5m / min, contact pressure is 5N), and dried (temperature is 60°C) to obtain a high molecular polymer film.
[0140] (3) Preparation of composite current collector: A 2 μm thick copper foil was plated on both sides of the polymer film in the thickness direction by vacuum plating to obtain a high-performance flame-retardant composite current collector.
[0141] The high-performance flame-retardant composite current collector is composed of a polymer film 2 and two metal layers 2021 arranged in the thickness direction of the polymer film 2; wherein the polymer film 2 is composed of a base film 202 and a flame-retardant layer 201 covering the base film 202; the base film 202 is provided with through holes 211 for ion transmission; the flame-retardant layer 201 contains flame-retardant particles 3, the flame-retardant particles 3 are prepared from closed-cell insulating polymer 311 and flame retardant 312, and the polymer shell 313 formed by the closed-cell insulating polymer 311 is coated on the outside of the flame retardant 312 to form particles with a core-shell structure.
[0142] Comparative Example 3
[0143] The preparation method of the current collector provided in this comparative example comprises the following steps:
[0144] 1. The phosphate flame retardant and PET are melt-blended, and the blended material is cast into a film to form a flame retardant substrate layer.
[0145] 2. The bonding layer 203 is made of aramid film, which is bonded to both sides of the flame retardant substrate layer by means of mechanical rolling.
[0146] 3. Vacuum evaporation is used to form a copper metal layer 202 on both sides of the adhesive layer 203 away from the flame retardant substrate layer.
[0147] 4. Use laser etching to form penetrating through holes in the layered structure formed in step 3), and then use electrochemical deposition to form a conductive coating made of graphite on the surface of the layered structure and the through holes.
[0148] Comparative Example 4
[0149] The structure diagram of the composite current collector provided in this comparative example is as follows Figure 5 As shown, the preparation method of the composite current collector comprises the following steps:
[0150] 1. PVDF was dissolved in NMP and prepared by solution casting to obtain a current collector support layer. PVDF was then dissolved in NMP and mixed with a heat-shrinkable thermosensitive conductive agent, bismuth-tin alloy, to prepare a suspension. A composite layer of a shrinkable thermosensitive conductive structure 3 and a current collector base layer 1 was prepared on both sides of the current collector support layer by solution casting. The shrinkable thermosensitive conductive structure 3 did not penetrate the base layer. The thickness of the PVDF layer as the current collector base layer 1 was 2 μm. The shrinkable thermosensitive conductive structure 3 was rod-shaped with a side length of 100 nm and a length of 3 μm.
[0151] 2. A gel precursor is coated on both sides of the composite layer, including a polyether polymer matrix ethylene glycol ethyl methacrylate and a flame retardant dimethyl phosphate, and the gel layer 201 is prepared after standing for 30 minutes. The thickness of the gel layer 201 is 1 μm.
[0152] 3. The aramid film is pressed onto the surface of the gel layer 201 by a mechanical roller to modify the adhesive layer 203, and the thickness of the adhesive layer 203 is 0.02 μm.
[0153] Test Case
[0154] After the composite current collectors in all the embodiments and comparative examples are used to make pole pieces, they are assembled with electrolyte and separator according to the following method to obtain a battery. The method includes:
[0155] 1) Mix lithium iron phosphate positive electrode powder (specific type of positive electrode material) with conductive agent Super P and binder PVDF in a weight ratio of 96.5:1:2.5, and obtain positive electrode slurry by dispersion. Coat the slurry on the composite current collector with a positive electrode surface density of 120g / m 2 Rolling is performed to prepare a positive electrode sheet;
[0156] 2) The graphite negative electrode is mixed with the conductive agent Super P and the binder CMC / SBR (1:1wt%) at a weight ratio of 97:1:2, and the mixture is dispersed in water and mixed by double planetary mixing to obtain a negative electrode slurry. The slurry is coated on the composite current collector, followed by roll pressing and drying to obtain a negative electrode sheet;
[0157] 3) Assemble the positive electrode sheet, negative electrode sheet and separator into a lithium-ion battery and inject non-aqueous electrolyte. The electrolyte component is lithium salt LiPF 6 , the solvent is EC and DEC, the additive is FEC, and the electrolyte formula is 1M LiPF 6 +EC:DEC(1:1wt%)+5wt%FEC.
[0158] 1. Acupuncture test
[0159] The batteries prepared according to the above method were tested in accordance with GB / T 31485-2015. The batteries that did not catch fire were considered to have passed. Ten batteries were tested in each group, and the pass rate was calculated. See Table 1 for details.
[0160] 2. Resistance test
[0161] The resistance test of the current collectors of all embodiments and comparative examples was carried out in accordance with GB / T 24343-2009. The test results are shown in Table 1.
[0162] 3. The mechanical properties of the current collectors of all embodiments and comparative examples were tested. The specific steps are as follows:
[0163] The current collector was cut into the following size: length * width * depth = 8 cm * 1.5 cm * 0.5 cm; the sample was loaded into a universal testing machine, and the test conditions were: test speed: 200 mm / min, gauge length: 25.00 mm, test temperature 20-30°C, test humidity: 30-60 RH%, and the test results are shown in Table 1.
[0164] Table 1
[0165]
[0166] According to Table 1, the composite current collectors provided in Examples 1-6 of the present invention have a puncture pass rate of not less than 50%, a resistance of not more than 76 mΩ, a tensile strength of not less than 54 MPa, and a fracture strength of not less than 37 MPa. Although the composite current collector provided in Comparative Example 4 also has a high puncture pass rate and mechanical strength, it is obvious that the resistance of the composite current collector provided in Comparative Example 4 is much higher than that of the composite current collectors provided in Examples 1-6, and cannot meet the demand for improving the conductive properties of the composite current collector. Therefore, the technical solution provided by the present invention can improve the conductive properties while meeting the safety performance, and has a certain mechanical strength to meet the use needs.
[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite current collector, characterized in that: It includes a current collector substrate, a first functional layer and a second functional layer respectively located on both sides of the current collector substrate, and N shrinkable thermosensitive conductive structures, where N is greater than or equal to 1; Wherein, in a direction gradually away from the current collector substrate, the first functional layer at least includes a gel layer and a metal layer stacked, and the second functional layer at least includes a gel layer and a metal layer stacked; The gel layer includes a polymer matrix and a flame retardant; When the application temperature is lower than the shrinkage temperature of the shrinkable thermosensitive conductive structure, the shrinkable thermosensitive conductive structure penetrates the first functional layer, the second functional layer, and the current collector base layer, and electrically connects the metal layer of the first functional layer and the metal layer of the second functional layer; When the application temperature is greater than the shrinking temperature, the shrinkable thermosensitive conductive structure shrinks, the metal layer of the first functional layer and the metal layer of the second functional layer are electrically disconnected, and the flame retardant is released.
2. The composite current collector according to claim 1, characterized in that: The shrinkage temperature of the shrinkable thermosensitive conductive structure is 90-150°C.
3. The composite current collector according to claim 1, characterized in that: The shrinkable thermosensitive conductive structure accounts for 20%-60% of the surface area of the composite current collector.
4. The composite current collector according to any one of claims 1 to 3, characterized in that: The mass ratio of the polymer matrix to the flame retardant is 1:(0.1%-5%).
5. The composite current collector according to claim 1, characterized in that: The first functional layer and the second functional layer further independently include an adhesive layer, and the adhesive layer is located between the gel layer and the metal layer; And / or, the bonding layer comprises at least one of aramid, polyethylene, hydroxyl-modified silicon oxide particles, and a mixture of silicon oxide and polyacrylic acid resin; And / or, the bonding layer has a thickness of 0.01-1 μm.
6. The composite current collector according to claim 1, characterized in that: The shrinkable thermosensitive conductive structure penetrates the current collector substrate and protrudes from the surface of the first functional layer; And / or, the shrinkable thermosensitive conductive structure penetrates the current collector substrate and protrudes from the surface of the second functional layer.
7. The composite current collector according to claim 6, characterized in that: The length of the shrinkable thermosensitive conductive structure protruding from the surface of the first functional layer is L1, and the thickness of the composite current collector is L, which satisfies: L1 / L=1% to 10%; And / or, the length of the shrinkable thermosensitive conductive structure protruding from the surface of the second functional layer is L2, and the thickness of the composite current collector is L, which satisfies: L2 / L=1% to 10%.
8. The composite current collector according to any one of claims 1 to 3, characterized in that: The material of the shrinkable thermosensitive conductive structure is selected from bismuth-tin alloy or tin-indium alloy; and / or, the polymer matrix comprises a cross-linked polymer containing an EO main chain and an amide group block; And / or, the flame retardant is a phosphorus-based flame retardant; And / or, the current collector substrate is selected from a PET layer or a PVDF layer; And / or, the metal layer is selected from copper or aluminum.
9. The composite current collector according to claim 1, characterized in that: The thickness of the current collector substrate is 1-10 μm; And / or, the gel layer has a thickness of 1-5 μm; And / or, the thickness of the metal layer is 0.01-1 μm; And / or, the shrinkable thermosensitive conductive structure has a length of 2.5-17 μm.
10. A pole piece, characterized in that: Comprising the composite current collector according to claim 1.
Citation Information
Patent Citations
Lithium ion battery composite pole piece, preparation method and lithium ion battery thereof
CN107507957A
Lithium ion battery, novel current collector and preparation method of novel current collector
CN112786895A
Thermal shrinkage composite current collector and application thereof
CN114497568A
Composite current collector and preparation method thereof
CN117832507A
Safety current collector
CN219998266U
Cited By
Negative current collector and preparation method thereof, pole piece and battery
CN120709380A